Domestic violence and mental health: a cross-sectional survey of women seeking help from domestic violence support services. Issue 1 (1st December 2016) - Ferrari, Giulia; Agnew-Davies, Roxane; Bailey, Jayne; Howard, Louise; Howarth, Emma; Peters, Tim J.; Sardinha, Lynnmarie; Feder, Gene Solomon
Abstract : Background: Domestic violence and abuse (DVA) are associated with increased risk of mental illness, but we know little about the mental health of female DVA survivors seeking support from domestic violence services. Objective: Our goal was to characterise the demography and mental health of women who access specialist DVA services in the United Kingdom and to investigate associations between severity of abuse and measures of mental health and health state utility, accounting for important confounders and moderators. Design: Baseline data on 260 women enrolled in a randomized controlled trial of a psychological intervention for DVA survivors were analysed. We report the prevalence of and associations between mental health status and severity of abuse at the time of recruitment. We used logistic and normal regression models for binary and continuous outcomes, respectively. The following mental health measures were used: Clinical Outcomes in Routine Evaluation – Outcome Measure (CORE-OM), Patient Health Questionnaire, Generalised Anxiety Disorder Assessment, and the Posttraumatic Diagnostic Scale to measure posttraumatic stress disorder (PTSD). The Composite Abuse Scale (CAS) measured abuse. Results: Exposure to DVA was high, with a mean CAS score of 56 (SD 34). The mean CORE-OM score was 18 (SD 8) with 76% above the clinical threshold (95% confidence interval: 70–81%). Depression and anxiety levels were high, with means close to clinical thresholds, and more than three-quarters of respondents recorded PTSD scores above the clinical threshold. Symptoms of mental illness increased stepwise with increasing severity of DVA. Conclusions: Women DVA survivors who seek support from DVA services have recently experienced high levels of abuse, depression, anxiety, and especially PTSD. Clinicians need to be aware that patients presenting with mental health conditions or symptoms of depression or anxiety may be experiencing or have experienced DVA. The high psychological morbidity in this population means that trauma-informed psychological support is needed for survivors who seek support from DVA services.